Analisis Prioritas Penyebab Masalah dalam Pemenuhan Standar Akreditasi 8.4 di Puskesmas Kraksaan - Selvia Juwita Swari; Gamasiano Alfiansyah; Wahyu Hidayati (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
Kraksaan Public Health Center got basic accreditation in 2017. The results of the accreditation standard 8.4 regarding MIRM have not been reached and must be improved for the next accreditation assessment. The purpose of this study is to analyze the priority causes of problems in the 8.4 accreditation standards at the Kraksaan Public Health Center. The method used is the MCUA (Multiple Criteria Utility Assessment). The results of identification of the organization of medical records in fulfillment of the 8.4 accreditation standard were 53.85% (partially fulfilled) with the lowest results in criterion 8.4.4 related to the completeness and confidentiality of medical records (16.67%) while based on the results of priority analysis of the causes of the problem related to the implementation of medical records in compliance with accreditation standards shows that there is no SOP on the implementation of assessments of the completeness and accuracy of the contents of medical records to be a top priority. The results of the study are efforts to improve the organization of medical records in fulfillment of the 8.4 accreditation standards in the form of making SOP assessing the completeness and accuracy of the contents of the medical records.